(untitled) (Damascus University Journal of agriculture sciences, 2025)
Colon cancer is a fundamental contributor to the death because of the cancer in general, as one million new death cases are caused by cancer (Hewish & Cunningham, 2011). Modern treatments of this disease are based on surgery treatment, radiation therapy, chemotherapy or all of them together, despite the benefit of these treatments, they have side effects that negatively affect patient´s health , especially chemotherapy and radiological therapy that are characterized by their toxicity to normal tissues in the body or by causing genetic mutations, to the cells or weaken the immune system in it, and it was found that there are many herbs that have shown a therapeutic ability for cancerous tumors. (Katz, 2002) In this research, the effect of saffron plant extract Crocus sativus was studied on the cell viability of colon cancer cell line CACO-2 and its behavior by studying its effect on cell migration so that it can be useful. The hydro alcoholic extraction of Crocus Sativus saffron stigmas was used, and the cancer cells of the CACO-2 cell line were cultured and incubated with different concentrations of saffron extract, and then cell viability was evaluated using the MTT assay as well as cell migration using the Wound healing assay in Vitro. The research was carried out in the ʺNational Commission for Biotechnologyʺ laboratories in Damascus. The results showed that the plant extract of Crocus sativus had a toxic effect on CACO-2 cells, and the inhibitory concentration was approximately 45%, 300µg/ml. This same concentration stimulates the migration of cancer cells, and the reason lies in what is called Epithelial to Mesenchymal Transition – EMT.